Corruption and the shadow economy: An empirical analysis - Axel Dreher; Friedrich Schneider (ETH Zurich, KOF Swiss Economic Institute, 2006)
This paper analyzes the influence of the shadow economy on corruption and vice versa. We hypothesize that corruption and shadow economy are substitutes in high income countries while they are complements in low income countries. The hypotheses are tested for a crosssection of 120 countries and a panel of 70 countries for the period 1994-2002. Our results show that the shadow economy reduces corruption in high income countries, but increases corruption in low income countries. We also find that stricter regulations increase both corruption and the shadow economy.
Keywords: D73; H26; O17; O5; 330; Corruption; Shadow Economy; Regulation; Tax Burden; Korruption; Schattenwirtschaft; Regulierung; Steuerbelastung; Schätzung; Welt